Root decomposition at high and low N supply throughout a crop rotation - Herrera, J. M. (2017)
Soil nitrogen (N) dynamics can be modified by cover crops in rotations with cereals. Although, roots are a major source of N, little is known about the dynamics of root decomposition of cash and cover crops. The objective of this study was to assess the effects that cover crop species have on i) the decomposition of spring wheat roots during the growth of cover crops, and ii) the decomposition of cover crop roots during the growing season of spring wheat. The experiment aimed also at comparing three non-winter hardy cover crops of varying shoot C/N ratios under low and high N input levels of 6 and 12 g N m−2 y−1, respectively. The experiment included spring wheat (Triticum aestivum L.) as the main crop and nonwinter hardy cover crops (yellow mustard (Sinapis alba L.), phacelia (Phacelia tanacetifolia Benth), and sunflower (Helianthus annuus L.) as well as bare soil fallow treatment. Minirhizotrons were used to nondestructively assess the spatial and temporal patterns of root growth and decomposition from 0.10 to 1.00 m. Simultaneously, we grew all crops in soil columns to measure destructively C and N contentin the roots. We concluded that wheat root decomposition was not affected by cover crop species. In contrast, during the growing season of wheat root decomposition of yellow mustard was on average twice as high for phacelia and sunflower as a consequence of a higher production of roots with a significantly higher C/N ratio compared to the other cover crops.